Tranformasi wayang kulit Seri Asun di Kampung Kunluang Jitra Kedah Darul Aman - Nor Azuan, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study aims to investigate and analyze the "Transformation of Wayang Kulit Seri Asun Kampung Kunluang Jitra Kedah". The objective of this study identified that there is a transformation of the congregation of wayang kulit Seri Asun, documenting the transformation of shadow Seri Asun shadow. The method used by the researchers is a method of qualitative and quantitative methods. This study used the Fan Theory(The Fan) by Richard Schechner (1977) in his book Performance Theory as a guide to produce this study. The findings could